4F-PBP (4′-fluoro-α-pyrrolidinobutyrophenone), a new substance of abuse: Structural characterization and purity NMR profiling. (July 2015) - Gaspar, Helena; Bronze, Soraia; Ciríaco, Sara; Queirós, Cláudio Rafael; Matias, Ana; Rodrigues, João; Oliveira, Cristina; Cordeiro, Carlos; Santos, Susana
Highlights: A new NPS, 4F-PBP was detected and identified for the first time in the EU. Analytical data for 4F-PBP are reported for the first time. Myo -inositol was found as cutting agent of 4F-PBP. A qNMR method was applied to profile cathinones purity. Abstract: The rapidly growing problem of new psychoactive substances (NPS) makes the time management for international control a real challenge, with the traditional detection methods becoming increasingly inadequate. NPS screening technologies, such as NMR, which allows multiple substances to be detected, characterized and quantified simultaneously from a single sample, offers a rapid solution to this problem. This study describes the application of NMR to the simultaneous detection, characterization and quantification of samples of white powders seized by the Portuguese Police. 4F-PBP (4′-fluoro-α-pyrolidinobutyrophenone) a new synthetic psychoactive cathinone cut with myo -inositol was found in two seized products. The structural characterization of 4F-PBP was elucidated in the mixture, and confirmed after isolation from the matrix by 1 H, 13 C, 19 F NMR and MS. Myo -inositol was found for the first time as a cutting agent of cathinones. Furthermore another seized product was characterized as being MDPBP, with a high degree of purity, and its spectroscopic elucidation enabled the correction of 13 C NMR literature assignments.